The Binary Toxin of Clostridioides difficile Alters the Proteome and Phosphoproteome of HEp-2 Cells - Stieglitz, Florian; Gerhard, Ralf; Pich, Andreas (Frontiers in Microbiology, 2021)
Clostridioides difficile is a major cause of nosocomial infection worldwide causing antibiotic-associated diarrhea and some cases are leading to pseudomembranous colitis. The main virulence factors are toxin A (TcdA) and toxin B (TcdB). Hypervirulent strains of C. difficile are linked to higher mortality rates and most of these strains produce additionally the C. difficile binary toxin (CDT) that possesses two subunits, CDTa and CDTb. The latter is responsible for binding and transfer of CDTa into the cytoplasm of target cells; CDTa is an ADP ribosyltransferase catalyzing the modification of actin fibers that disturbs the actin vs microtubule balance and induces microtubule-based protrusions of the cell membrane increasing the adherence of C. difficile. The underlying mechanisms remain elusive. Thus, we performed a screening experiment using MS-based proteomics and phosphoproteomics techniques. Epithelial Hep-2 cells were treated with CDTa and CDTb in a multiplexed study for 4h and 8h. Phosphopeptide enrichment was performed using affinity chromatography with TiO2 and Fe-NTA; for quantification, a TMT-based approach and DDA measurements were used. More than 4,300 proteins and 5,600 phosphosites were identified and quantified at all time points. Although only moderate changes were observed on proteome level, the phosphorylation level of nearly 1,100 phosphosites responded to toxin treatment. The data suggested that CSNK2A1 might act as an effector kinase after treatment with CDT. Additionally, we confirmed ADP-ribosylation on Arg-177 of actin and the kinetic of this modification for the first time.